Combined universal and selective prevention for adolescent alcohol use: a cluster randomized controlled trial. Issue 10 (22nd February 2017) - Teesson, M.; Newton, N. C.; Slade, T.; Carragher, N.; Barrett, E. L.; Champion, K. E.; Kelly, E. V.; Nair, N. K.; Stapinski, L. A.; Conrod, P. J.
Abstract : Background: No existing models of alcohol prevention concurrently adopt universal and selective approaches. This study aims to evaluate the first combined universal and selective approach to alcohol prevention. Method: A total of 26 Australian schools with 2190 students (mean age: 13.3 years) were randomized to receive: universal prevention ( Climate Schools ); selective prevention ( Preventure ); combined prevention ( Climate Schools and Preventure ; CAP ); or health education as usual (control). Primary outcomes were alcohol use, binge drinking and alcohol-related harms at 6, 12 and 24 months. Results: Climate, Preventure and CAP students demonstrated significantly lower growth in their likelihood to drink and binge drink, relative to controls over 24 months. Preventure students displayed significantly lower growth in their likelihood to experience alcohol harms, relative to controls. While adolescents in both the CAP and Climate groups demonstrated slower growth in drinking compared with adolescents in the control group over the 2-year study period, CAP adolescents demonstrated faster growth in drinking compared with Climate adolescents. Conclusions: Findings support universal, selective and combined approaches to alcohol prevention. Particularly novel are the findings of no advantage of the combined approach over universal or selective prevention alone.